2016
DOI: 10.1523/jneurosci.1699-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Selective Neuronal Activation by Cochlear Implant Stimulation in Auditory Cortex of Awake Primate

Abstract: Despite the success of cochlear implants (CIs) in human populations, most users perform poorly in noisy environments and music and tonal language perception. How CI devices engage the brain at the single neuron level has remained largely unknown, in particular in the primate brain. By comparing neuronal responses with acoustic and CI stimulation in marmoset monkeys unilaterally implanted with a CI electrode array, we discovered that CI stimulation was surprisingly ineffective at activating many neurons in audi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 79 publications
1
22
1
Order By: Relevance
“…Recordings of singleneuron firing in AI confirmed this energy threshold. A recent study in awake primates demonstrated that about 40% of neurons in the auditory cortex could be driven by contralateral eCI stimulation (27), whereas we observed 52% of neurons driven by oCI in the gerbil.…”
Section: Discussioncontrasting
confidence: 88%
“…Recordings of singleneuron firing in AI confirmed this energy threshold. A recent study in awake primates demonstrated that about 40% of neurons in the auditory cortex could be driven by contralateral eCI stimulation (27), whereas we observed 52% of neurons driven by oCI in the gerbil.…”
Section: Discussioncontrasting
confidence: 88%
“…Taken together, these data suggest that the marmoset AC in the study by Johnson et al (2016) has a history of experience with real sounds but not the kind of stimulation produced by CIs. Future experiments using the CI marmoset model could test the hypothesis that O-units are important for CI performance in noisy surroundings.…”
mentioning
confidence: 75%
“…Each neuron was tested for both acoustic and CI responsiveness with a range of repetition or stimulation rates and sound or current levels (see Materials and Methods). Note that a neuron could be responsive to both acoustic and CI stimulation or only one modality (Johnson et al, 2016). After finding a CI stimulus that evoked firing in the neuron, an electrode-tuning function (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 187 were responsive to CI pulse trains and 237 were responsive to acoustic click trains. Our recent work showed that the left hemisphere (contralateral to CI) was much more responsive to CI than the right hemisphere (Johnson et al, 2016). Therefore, the population data of CI-responsive units consisted of 159 units from left hemispheres and 28 units from right hemispheres.…”
Section: Methodsmentioning
confidence: 99%